Validated age-specific reference values for CSF total protein levels in children. (July 2017) - Kahlmann, V.; Roodbol, J.; van Leeuwen, N.; Ramakers, C.R.B.; van Pelt, D.; Neuteboom, R.F.; Catsman-Berrevoets, C.E.; de Wit, M.C.Y.; Jacobs, B.C.
Abstract: Objective: To define age-specific reference values for cerebrospinal fluid (CSF) total protein levels for children and validate these values in children with Guillain-Barré syndrome (GBS), acute disseminated encephalomyelitis (ADEM) and multiple sclerosis (MS). Methods: Reference values for CSF total protein levels were determined in an extensive cohort of diagnostic samples from children (<18 year) evaluated at Erasmus Medical Center/Sophia Children's Hospital. These reference values were confirmed in children diagnosed with disorders unrelated to raised CSF total protein level and validated in children with GBS, ADEM and MS. Results: The test results of 6145 diagnostic CSF samples from 3623 children were used to define reference values. The reference values based on the upper limit of the 95% CI (i.e. upper limit of normal) were for 6 months–2 years 0.25 g/L, 2–6 years 0.25 g/L, 6–12 years 0.28 g/L, 12–18 years 0.34 g/L. These reference values were confirmed in a subgroup of 378 children diagnosed with disorders that are not typically associated with increased CSF total protein. In addition, the CSF total protein levels in these children in the first 6 months after birth were highly variable (median 0.47 g/L, IQR 0.26–0.65). According to these new reference values, CSF total protein level was elevated in 85% of children with GBS, 66% with ADEM and 23% with MS. Conclusion: More accurate age-specific reference values for CSF total protein levels in children were determined. These new reference values are more sensitive than currently used values for diagnosing GBS and ADEM in children. Highlights: CSF protein levels in children are normally lower than in adults. Improved age-dependent reference values for CSF protein in children were defined. New reference values increase sensitivity to diagnose pediatric GBS, ADEM and MS.